TYPE-I ASSEMBLY LINE BALANCING WITH WORKLOAD SMOOTHING - Zengin, Harun; Selcuk Kilic , Huseyin (MATTER: International Journal of Science and Technology, 2024)
Balancing the assembly lines plays an important role in increasing the productivity of the manufacturing systems. Depending on the objectives, there are various types of this problem. In this study, a Type-1 assembly line balancing problem is considered. It is known that the distribution of workload and equal distribution of idle time in station balancing is important for worker motivation and ergonomics. Once the number of stations is minimized, which is the primary objective in solving a Type-1 problem, the optimum solution found should be analyzed in terms of the smoothness index. Otherwise, the idle time can be distributed unevenly to the stations. Hence, one of the classical problems in assembly line balancing literature, Sawyer problem, is considered in this study. Firstly, the problem is solved via integer programming with Gurobi in Python. In the second stage, the line was smoothed via two techniques including the classical one and the proposed min-max approach. Different cycle times are tested and a comparison is provided for the two techniques.